2006
DOI: 10.1007/bf02914072
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism of NaClO3 and NaBrO3 crystals from aqueous solutions

Abstract: A study of growth rates of NaClO 3 and NaBrO 3 has been carried out using a small growth cell by in situ observation. Normal growth rates of {100} faces of NaClO 3 and {111} faces of NaBrO 3 along 〈 〈110〉 〉 direction are measured under relatively high supersaturation ranging from 3-8%. In the initial stages of growth, {100}, {110} and {111} faces develop in NaClO 3 and gradually all the faces are replaced by the {100} faces only. In the case of NaBrO 3 , mostly {111} faces develop with occasional occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Both from visual observation of the fits and SSR values, it can be concluded that the B + S model fits much better the whole experimental dataset as compared to the BCF and PL models. This indicates that at the conditions examined, the B + S growth mechanism describes the observed growth behavior of sodium chlorate more accurately, which is in agreement with previous in situ microscopy studies , in which no growth spirals characteristic of BCF mechanism could be observed, while concentric patterns of growth hillocks typical to two-dimensional nucleation were clearly seen.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Both from visual observation of the fits and SSR values, it can be concluded that the B + S model fits much better the whole experimental dataset as compared to the BCF and PL models. This indicates that at the conditions examined, the B + S growth mechanism describes the observed growth behavior of sodium chlorate more accurately, which is in agreement with previous in situ microscopy studies , in which no growth spirals characteristic of BCF mechanism could be observed, while concentric patterns of growth hillocks typical to two-dimensional nucleation were clearly seen.…”
Section: Resultssupporting
confidence: 90%
“…Indicatively, Radisǎ et al 47 measured a growth rate of 3 × 10 −8 m s −1 for σ 1 = 0.015, while Matsunaka et al 44 conclude to a growth rate of 4.8 × 10 −8 m s −1 for σ 1 = 0.029. In addition, Surender et al 46 report a growth rate of approximately 2.5 × 10 −8 m s −1 for σ 1 = 0.025, which is very close to the results of Wojciechowski et al, 50 while for σ 1 = 0.015, the same authors report a value of ca. 1.6 × 10 −8 m s −1 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Ristić et al showed that for sodium chlorate crystals in supersaturation range of 0.1–1.0% ( R , σ) dependence might be parabolic or linear. Surender et al showed that at supersaturations of 3–8% a parabolic trend appeared, suggesting a two-dimensional mechanism.…”
Section: Introductionmentioning
confidence: 99%